The Effect Of Customer Relationship Management (CRM) On Customer Satisfaction In PT.Telkom Indonesia Tbk, Surakarta - Abushamsiya, Hamza, Ikhwan Susila, Ph.D (2017)
This paper examined the effect of customer relationship management elements on customer satisfaction through empirical study of telecommunication service in PT.Telkom in Surakarta city. This study aims to determine the influence of quality of service, employee behavior and customer solving problem on customer satisfaction. Data were collected using questionnaire-based survey consisting of 15 questions and distributed to 150 respondents comprising all of Telkom company customers in Surakarta city. In order to analyze the data obtained from questionnaires, quantitative methods were employed. The findings showed that customer relationship management elements have a significant effect on customer satisfaction. Finally, the study recommends that management should improve the customer relationship management by applying the right project of customer relationship management to gain high customer satisfaction.